Perspectives on Outpatient Delivery of Bispecific T-Cell Engager Therapies for Multiple Myeloma - Andrée-Anne Pelland; Mathilde Dumas; Émilie Lemieux-Blanchard; Richard LeBlanc; Julie Côté; Jean-Samuel Boudreault; Dominic Duquette; Rayan Kaedbey; Marc Lalancette; Frédéric Larose; Anna Nikonova; Michel Pavic; et al. (Current Oncology)
In the past few years, a new promising therapy, called bispecific T-cell engager (TCE), has been developed and is now available in many countries for patients with relapsed or refractory multiple myeloma. T-cell engagers are associated with sustained efficacy and progression-free survival benefits in patients with heavily treated myeloma. However, complications such as cytokine release syndrome (CRS), immune effector cell-associated neurotoxicity syndrome (ICANS), and infections complicate their administration, particularly in remote centers. This review discusses the key requirements for delivering TCEs therapies, focusing on outpatient delivery. We also outline the primary acute and chronic complications of TCE therapy and their management.